National Development and the Place of Multi-Languages: Nigeria in Focus - Duru, Lilian Oluchi; Onyinyechi, Udushirinwa Ijeoma; Nonye, Nnani Henrietta (Journal of Legal and Cultural Analytics, 2024)
Difference in Languages been an issue of growing social importance because a majority of all living languages are threaded in their continued existence, the aim of this study is to appreciate the idea of different languages may be as an instrument of national development and wealth creation, the meeting point between Multilanguage and national Development, to give it some valuable suggestions which might be of help in language planning in multi-language and multicultural setting like Nigeria, to buttress this point, this study some questionnaires, of which the respondents were a total of one hundred copies were collected for the research, the respondent are the students of English department and from other departments in Abia State University. A percentage and a frequency table, the data were properly analyzed. The outcome or result obtained showed that multilingualism or linguistic diversity did not project or promote disintegration in the country; rather the linguistics diversity in Nigeria has been a national resource which help to move the country forward and not taking multilingualism to be an instrument for national disintegration. In conclusion, the researcher made some recommendations that both the people at the helm of affairs should help in promoting national development through the use of multilingual policy in the country and the dissemination of information materials to the public like newspapers, posters, computer application and hold programmes to promote multilingualism.